Understanding the relationship between mental models, conflict and conflict asymmetry. Issue 7 (12th October 2015) - Bergiel, Erich B.; Gainey, Thomas W.; Bergiel, Blaise J.
Abstract : Purpose: – The purpose of this study is to test theoretically based hypotheses linking task and team-shared mental models (SMMs) with multiple dimensions of conflict and conflict asymmetry. SMMs are viewed as an underlying mechanism of team processes. While current research has begun to clarify their influence on functional team processes, their influence on dysfunctional processes is still unknown. Design/methodology/approach: – The survey was administered to 17 graduate business classes working on intense semester-long group projects. A total of 295 individual responses were received which comprised 90 ( N = 90) teams. Findings: – Results suggest that team SMMs reduce all dimensions of conflict and relationship conflict asymmetry, while task SMMs increase all dimensions of conflict and relationship conflict asymmetry. Research limitations/implications: – This study captured the influence of SMMs on conflict at one stage of group development. Future research should examine the impact of SMMs on conflict at multiple stages of group development. Originality/value: – This study contributes to the literature on both mental models and conflict. In addition, based on our literature review, it was the first to empirically link SMMs and conflict asymmetry.